Nose stud screw aspirationa - a tiny foreign body with potentially huge disaster: 2 cases with different ways of retrieval - Ng, Khai Lip; Huan, Nai Chien; Daut, Ummi Nadira; Muhammad, Noorul Afidza; Nasaruddin, Mona Zaria; Abdul Rahaman, Jamalul Azizi (The Interventionalist, 2022)
Foreign body aspiration refers to accidental inhalation of foreign body into the respiratory tract. More commonly observed in children, foreign body aspiration is less common in adults. Traditionally observed amongst Indian women, nose piercing and jewelleries are gaining popularity in various communities for the past decade. Aspiration of tiny nose jewelleries such as nose stud screws is a serious and potentially fatal event. Small foreign bodies may dislodge further into the subsegmental bronchus, rendering bronchoscopic retrieval technically challenging. Herein, we report the first 2 cases of nose stud screw aspiration. Both of our patients were asymptomatic. Both foreign bodies were successfully retrieved via bronchoscopy using different tools and methods.